Longitudinal bidirectional associations between personality and becoming a leader. Issue 2 (16th May 2022) - Asselmann, Eva; Holst, Elke; Specht, Jule
Abstract: Objective: Leaders differ in their personalities from non‐leaders. However, when do these differences emerge? Are leaders "born to be leaders" or does their personality change in preparation for a leadership role and due to increasing leadership experience? Method: Using data from the German Socio‐Economic Panel Study, we examined personality differences between leaders (N = 2683 leaders, women: n = 967; 36.04%) and non‐leaders (N = 33, 663) as well as personality changes before and after becoming a leader. Results: Already in the years before starting a leadership position, leaders‐to‐be were more extraverted, open, emotionally stable, conscientious, and willing to take risks, felt to have greater control, and trusted others more than non‐leaders. Moreover, personality changed in emergent leaders: While approaching a leadership position, leaders‐to‐be (especially men) became gradually more extraverted, open, and willing to take risks and felt to have more control over their life. After becoming a leader, they became less extraverted, less willing to take risks, and less conscientious but gained self‐esteem. Conclusions: Our findings suggest that people are not simply "born to be leaders" but that their personalities change considerably in preparation for a leadership role and due to leadership experience. Some changes are transient, but others last for a long time.